2017
DOI: 10.1007/s12015-017-9745-1
|View full text |Cite
|
Sign up to set email alerts
|

A Singular Role of IK1 Promoting the Development of Cardiac Automaticity during Cardiomyocyte Differentiation by IK1 –Induced Activation of Pacemaker Current

Abstract: The inward rectifier potassium current (IK1) is generally thought to suppress cardiac automaticity by hyperpolarizing membrane potential (MP). We recently observed that IK1 could promote the spontaneously-firing automaticity induced by upregulation of pacemaker funny current (If) in adult ventricular cardiomyocytes (CMs). However, the intriguing ability of IK1 to activate If and thereby promote automaticity has not been explored. In this study, we combined mathematical and experimental assays and found that on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 53 publications
1
20
0
Order By: Relevance
“…Similar results were observed in the 1Hz paced condition (Supplementary Figure 2). Given its importance in automaticity (Azene et al, 2005;Tse et al, 2006;Xue et al, 2007;Lieu et al, 2008;Sun et al, 2017), we next measured the funny current (I f ) in hESC-VCMs isolated from hvCAS. Representative tracings were shown in Figure 3A.…”
Section: Electrophysiological Basis Of the Effect Of T3-ec Treatment mentioning
confidence: 99%
“…Similar results were observed in the 1Hz paced condition (Supplementary Figure 2). Given its importance in automaticity (Azene et al, 2005;Tse et al, 2006;Xue et al, 2007;Lieu et al, 2008;Sun et al, 2017), we next measured the funny current (I f ) in hESC-VCMs isolated from hvCAS. Representative tracings were shown in Figure 3A.…”
Section: Electrophysiological Basis Of the Effect Of T3-ec Treatment mentioning
confidence: 99%
“…HEK293 cell (44) and Kir2.1/HCN4 (42) showed that I K1 may actually recruit more I f by activating current at more negative membrane voltages, because I K1 was the only negative current in these experiments. Our simulation, however, did not yield such a result because the interaction of other positive currents (such as I NaK , I Kr and I Ks ) contributed to the hyperpolarization of membrane potential and helped the activation of I f .…”
Section: /Hcn2mentioning
confidence: 80%
“…I f has been shown to play an important role in generating pacemaking APs in both native (13,21,27,28,35,36) and engineered pacemakers (42). Experimentally it has been shown that high expression of HCN2 can initiate spontaneous beats in neonatal rat VMs (21,35) and improve spontaneous beats in rabbit CMs (13).…”
Section: Role Of I F In Pacemaking Activitymentioning
confidence: 99%
See 2 more Smart Citations